Struktur Pasar dan Daya Saing Ekspor Nanas Olahan Indonesia ke Pasar Jepang (Jurnal Agribisnis Indonesia, 2025)
Japan is an export destination for processed pineapple with great potential. This can be seen from the high demand for this tropical commodity in the Japanese market. Although the Indonesia-Japan Economic Partnership Agreement (IJEPA) should open up greater opportunities for processed pineapple exports, Indonesia has not optimally utilized it. This is reflected in the fluctuating trend of Indonesia's processed pineapple exports, which have tended to decline in recent years. In addition, the dominance of other countries such as the Philippines and Thailand has caused Indonesia to only act as a market follower. This study aims to identify the market structure and analyze the competitiveness of Indonesian processed pineapple exports in the Japanese market compared to the Philippines, Thailand, and Malaysia. Market structure analysis was conducted using Concentration Ratio (CR4) and Herfindahl-Hirschman Index (HHI). Meanwhile, competitiveness was analyzed by Revealed Comparative Advantage (RCA), Export Product Dynamic (EPD), and Index of Trade Specialization (ISP). The results showed that the market structure of processed pineapple in Japan is oligopolistic with high concentration. Indonesian processed pineapple has a comparative advantage in the Japanese market with an average RCA value of 6.43. On the other hand, there is a competitive advantage possessed by Indonesian processed pineapple, but less dynamic shown in the Falling Star category. In addition, the results of the ISP analysis show that Indonesia is a processed pineapple exporting country in the international market.